Usage and Diffusion of Cellular Telephony, 1998-2004 - Michał Grajek; Tobias Kretschmer (European School of Management and Technology (ESMT), 2007)
We study the dynamics of usage intensity of second-generation cellular telephony over the diffusion curve. Specifically, we address two questions: First, can we draw conclusions about the underlying drivers of technology diffusion by studying usage intensity? Second, what is the effect of high penetration of previous generations and competing networks on network usage intensity? Using an operator-level panel covering 41 countries with quarterly data over 6 years, we find that heterogeneity among adopters dominates network effects and that different technological generations are complements in terms of usage, but substitutes in terms of subscription.
urn:nbn:de:101:1-201106143418
Keywords: L1; L52; O38; 650; Cellular telephony; diffusion; usage intensity; network effects; consumer heterogeneity; fixed-mobile substitutability